Winding back Wnt signalling: Potential therapeutic targets for treating gastric cancers - Flanagan, D.; Vincan, Elizabeth; Phesse, T. (John Wiley & Sons, 2017)
© 2017 The British Pharmacological Society. Gastric cancer persists as a frequent and deadly disease that claims over 700000 lives annually. Gastric cancer is a multifactorial disease that is genetically, cytologically and architecturally more heterogeneous than other gastrointestinal cancers, making it therapeutically challenging. As such, and largely attributed to late-stage diagnosis, gastric cancer patients show only partial response to standard chemo and targeted molecular therapies, highlighting an urgent need to develop new targeted therapies for this disease. Wnt signalling has a well-documented history in the genesis of many cancers and is, therefore, an attractive therapeutic target. As such, drug discovery has focused on developing inhibitors that target multiple nodes of the Wnt signalling cascade, some of which have progressed to clinical trials. The collective efforts of patient genomic profiling has uncovered genetic lesions to multiple components of the Wnt pathway in gastric cancer patients, which strongly suggest that Wnt-targeted therapies could offer therapeutic benefits for gastric cancer patients. These data have been supported by studies in mouse models of gastric cancer, which identify Wnt signalling as a driver of gastric tumourigenesis. Here, we review the current literature regarding Wnt signalling in gastric cancer and highlight the suitability of each class of Wnt inhibitor as a potential treatment for gastric cancer patients, in relation to the type of Wnt deregulation observed.